2011
DOI: 10.1007/s10067-010-1667-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac tamponade and large pericardial effusions in systemic sclerosis

Abstract: Cardiac tamponade in systemic sclerosis is rare. We report four cases of SSc with hemodynamically significant pericardial effusions associated with pulmonary arterial hypertension, three of whom died, two following pericardiocentesis. Of 26 SSc cases reported in the literature with large pericardial effusions, seven were associated with PAH. Including our series, the mortality rate is 55%.The potential contributory role of PAH in the development of pericardial effusion and the management implications are explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 29 publications
1
31
0
6
Order By: Relevance
“…First, the standard of care for treatment of patients with pericardial tamponade and impending hemodynamic collapse has been pericardial drainage (1,3,4,6) either percutaneously by pericardiocentesis or by surgical decompression. Previously reported data by Hemnes et al (6) suggested that the one year mortality of PH patients with hemodynamically significant pericardial effusion in the absence of intervention may be 50%, and that the perioperative mortality associated with operative intervention in their patient population was also 50% (one of two patients died).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the standard of care for treatment of patients with pericardial tamponade and impending hemodynamic collapse has been pericardial drainage (1,3,4,6) either percutaneously by pericardiocentesis or by surgical decompression. Previously reported data by Hemnes et al (6) suggested that the one year mortality of PH patients with hemodynamically significant pericardial effusion in the absence of intervention may be 50%, and that the perioperative mortality associated with operative intervention in their patient population was also 50% (one of two patients died).…”
Section: Discussionmentioning
confidence: 99%
“…PAH due to connective tissue disease such as scleroderma with pericardial effusion may confer additional risk (2, 3, 4) Data from the REVEAL registry suggest the prevalence of pericardial effusion among WHO diagnostic class 1 PAH patients may be as high as 25% (2) Pericardiocentesis or surgical pericardial window have been used for refractory, recurrent, or hemodynamically unstable pericardial effusions due to a wide range of etiologies (1) . A case series of six PAH patients with pericardial tamponade revealed 50% mortality over one year period if effusion was not drained and of two patients who received intervention for effusion with pericardial window (PW) placement (5) , one patient expired.…”
Section: Introductionmentioning
confidence: 99%
“…In general, draining pericardial effusions should be avoided. Although anecdotal case reports suggest that opening of the pericardium may improve cardiac function (85), two small series reported 50% mortality in patients who had their effusion drained (86,87).…”
Section: Percutaneous Interventionsmentioning
confidence: 99%
“…Although pericardial disease has been majorly described in association with renal failure in as many as 2/3rd of patients, some patients may develop fibrofibrinous pericarditis for which no other apparent cause is evident. Pericardial effusion presenting with tamponade could be attributable to the presence of severe pulmonary arterial hypertension with or without underlying lung disease 4. In this case the mortality may be as high as 55%.…”
Section: Discussionmentioning
confidence: 96%